IL-22 signaling promotes sorafenib resistance in hepatocellular carcinoma via STAT3/CD155 signaling axis - Chen, Junzhang; Sun, Shiran; Li, Hui; Cai, Xiong; Wan, Chidan (Frontiers in Immunology, 2024)
Sorafenib is currently the first-line treatment for patients with advanced hepatocellular carcinoma (HCC). Nevertheless, sorafenib resistance remains a huge challenge in the clinic. Therefore, it is urgent to elucidate the mechanisms underlying sorafenib resistance for developing novel treatment strategies for advanced HCC. In this study, we aimed to investigate the role and mechanisms of in sorafenib resistance in HCC. The in vitro experiments using HCC cell lines and in vivo studies with a nude mouse model were used. Calcium staining, chromatin immunoprecipitation, lactate dehydrogenase release and luciferase reporter assays were employed to explore the expression and roles of IL-22, STAT3 and CD155 in sorafenib resistance. Our clinical results demonstrated a significant correlation between elevated IL-22 expression and poor prognosis in HCC. Analysis of transcriptomic data from the phase-3 STORM-trial (BIOSTORM) suggested that STAT3 signaling activation and natural killer (NK) cell infiltration may associate sorafenib responses. STAT3 signaling could be activated by IL-22 administration in HCC cells, and then enhanced sorafenib resistance in HCC cells by promoting cell proliferation and reducing apoptosis in vitro and in vivo. Further, we found IL-22/STAT3 axis can transcriptionally upregulate CD155 expression in HCC cells, which could significantly reduce NK cell-mediated HCC cell lysis in a coculture system. Collectively, IL-22 could contribute to sorafenib resistance in HCC by activating STAT3/CD155 signaling axis to decrease the sensitivities of tumor cells to sorafenib-mediated direct cytotoxicity and NK cell-mediated lysis. These findings deepen the understanding of how sorafenib resistance develops in HCC in terms of IL-22/STAT3 signaling pathway, and provide potential targets to overcome sorafenib resistance in patients with advanced HCC.